English is Fun! – English Strange and Funny: The Development of E – Learning System for Secondary School Student - MD SAID, FAQIHAH; RAMLI, AZIZUL AZHAR (Applied Information Technology And Computer Science, 2023)
Vocabulary is one of the most comprehensive but difficult aspect of English for foreign learners to master thoroughly including the words categorized as homophone and homograph. Homophone refers to any word with the same pronunciation as another word but has a different meaning and spelling whereas, Homograph refers to words with the same spelling but different pronunciation and meaning. However, most Malaysian students cannot speak English confidently due to lack of vocabulary. Students’ limited knowledge of English words is one reason they are not well-versed in the existence of different words in English. Hence, an E – Learning System for Secondary School Student is developed. The main objective is to design English E – Learning System using structures and web system approach. This system is targeted to secondary school students aged 16 years old. ADDIE models are used to conduct this study and a few software’s are used to develop the system. This project will be conducted to allow students learn homophone and homograph in English language and so will help them to have a wide range of vocabulary.